HUMAN RESOURCE PLANNING: THE LIFE DIRECTION OF EDUCATIONAL ORGANIZATIONS IN INDONESIA - Hidayatullah, Hidayatullah; Rafid, Reni Haryani; Marsyaoly, Muhammad Isya (Four Son Scholarship, 2023)
Human resource planning is very important for the future of an organization. Therefore it is very effective if an institution or organization implements human resource planning in selecting prospective members who will contribute to the organization. Educational institutions are one of the organizations that require human resource planning to process the organization based on forecasts and the need for human resources, then after that provide education and training to develop and improve the capabilities of the resources they have. This paper describes with a qualitative perspective on human resource planning (Human Resources Planning) in determining the direction of life of a public organization from the point of view of human resource planning in a public institution or organization, in this case an educational institution which is a public organization that is expected to have management. good, adaptive and flexible resources so as to produce quality and proactive resources in achieving organizational goals